Comparison of in vitro anti-Staphylococcus aureus activity of eight antibiotics and four dilutions of propolis - Ken Jact Fernández-León; José Antonio Rodríguez-Díaz; Lisandra Reyes-Espinosa; Amílcar Duquesne-Alderete; Yovanni Orestes Solenzal-Valdivia; Alayn Rives-Quintero; Juan Emilio Hernández-García (Journal of the Selva Andina Research Society)
The objective of this research was based on the comparison of inhibition halos of a sample of Staphylococcus aureus, faced in vitro with eight antibiotics used in medicine, as well as four alcoholic concentrations of propolis. The results indicate that the antimicrobial action of propolis, depending on the bioactive compounds such as: flavonoids, polyphenols, aromatic acids, etc., contained in this product. The antibacterial activity of the four propolis dilutions produced inhibition halos between 10 and 20 mm. Of the eight antibiotics with which the comparison was made, only erythromycin was found to be resistant to S. aureus. Penicillin produced halos with smaller dimensions. Although the halos derived from the rest of the antimicrobials were greater than those from propolis, many of them were found within the range originated by said product from the hive. Compared antibacterial resistance has not been demonstrated, with which over the year’s antibiotics present, when used indiscriminately to eliminate or control antimicrobial agents